THE DEVELOPMENT OF A SCIENTIFIC THEORY OF AUDIT IS A REQUIREMENT OF TIME (INNOVATIVE ECONOMY, 2022)
Pushkar M.S. THE DEVELOPMENT OF A SCIENTIFIC THEORY OF AUDIT IS A REQUIREMENT OF TIMEPurpose. The aim of the article is to form a modern theoretical model (system) of auditing to improve the practical work of auditors.Methodology of research. The content of the article is based on the use of such a scientific apparatus as the historical method (when studying the process of the history of the emergence of audit needs), the monographic method and the method of historical development (based on the analysis of the formation of the modern theoretical audit model, the dialectic of changes in the audit environment and its formation on the basis of a set of philosophical , sociological, systemic, psychological and other approaches and methods of cognition), system and analytic – when processing the received information.Findings. The evolution of audit development is analysed depending on the accounting needs and production processes of the enterprise. It has been proven that an audit is a set of various empirical rules and procedures for the verification and assessment of the level of compliance of indicators of the desired and actual state of the object, for which individual persons are responsible. It was revealed that in connection with the changes in the accounting system, the conceptual basis of the audit should be clarified in terms of the theoretical base, organizational structure, and methodology of the study of the economic activity of the enterprise.Originality. The author substantiated the audit model, which can influence practical activity and determine its usefulness for business, which involves revealing the essence of audit, structure and axiology (values) for the economy of the country and enterprises.Practical value. The author’s proposals can be used as a methodical guideline for the implementation of the idea of practical use of audit in the organization of the internal control structure, which would guarantee the effective work of the company’s personnel at all stages of the technological process of production and its management.Key words: business, system, accounting, audit, model, auditor, paradigm.
Keywords: business; system; accounting; audit; model; auditor; paradigm